Development and characterization of a new embedded ionic liquid based membrane-cathode assembly for its application in single chamber microbial fuel cells. (15th December 2015) - Ortiz-Martínez, V.M.; Salar-García, M.J.; Hernández-Fernández, F.J.; de los Ríos, A.P.
Abstract: The search for alternative materials for their application in MFCs (microbial fuel cells) has become one of the main concerns among researchers in order to improve their efficiency. This work focuses on the development and optimization of a method for preparing a novel embedded membrane-cathode assembly based on ILs (ionic liquids) for its application in single-chamber MFCs. The assembly showed in the present article consists of embedding a polymer inclusion membrane based on the IL methyltrioctylammonium chloride into a carbon cloth cathode. The performance of this design is compared with that provided by an IL-based membrane placed between the anode and a carbon cloth electrode after being manufactured separately. Four step-by-step sequences for embedding the membrane are investigated to optimize its implementation. The new assembly was characterized by SEM-EDX and Mapping and assessed in single-chamber MFCs, allowing the power density to be increased from 51.5 mW m −3 with a Coulombic efficiency of 19.18% to 613.3 mW m −3 with a Coulombic efficiency of 64.96% for the ionic liquid investigated, which represents a significant improvement in terms of energy generation. This assembly also offers more compact and simpler design versus those configurations including IL-based membranes and electrodes as separate components in MFCs. Highlights: New embedded IL-based membrane-cathode assembly for single-chamber MFCs. Improvement of MFC performance with embedded membranes. Optimization of the method for embedding the membrane into the cathode. Embedded membrane-cathode assembly offers simpler and more compact design.